Variable delay digital comb filter extraction of weak phase signals for SSVEP. (January 2017) - Chang, Chih-Tsung; Lee, Po-Lei; Lin, En-Hung
Highlights: We propose that comb filter can be eliminated phase noise. Using a variable delay (VD) can be achieved fractional delay time and it is easily adjusted the frequency of a digital comb filter. The results show that comb filters had a higher SNR of phase signal. Phase signals in EEG are clearly separated without overlap. Abstract: This study presents denoising of phases signal by comb filter. Signal phase is widely used in biomedical and communications engineering, and has become increasingly important over the past few years. In particular, steady-state visual evoked potential (SSVEP) of electroencephalogram (EEG) and quadrature amplitude modulation (QAM) uses phase to distinguish channel and data. For signal processing, the filter is usually adopted. In this study, the usefulness of comb and bandpass filters in detecting the phase of a signal is compared by using simulated and real signals to verify phase signal denoising. Experimental data show that comb filters had a higher signal to noise ratio (SNR) of phase signal. However, even if a comb filter performs well, the delay time of a digital comb filter will be limited by the sampling rate. It is possible to solve this problem, but doing so is inconvenient within the context of real-time applications. Using a variable delay (VD) approached to fractional delay for digital comb filter, it is both simple and easy to use.